Identification and Validation of Hub Genes in Acute Pancreatitis and Hypertriglyceridemia - Zhang S; Liang Z; Xiang X; Liu L; Yang H; Tang G (Diabetes, Metabolic Syndrome and Obesity, 2022)
Shiyu Zhang, Zhihai Liang, Xuelian Xiang, Li Liu, Huiying Yang, Guodu Tang Department of Gastroenterology, The First Affiliated Hospital of Guangxi Medical University, Nanning City, Guangxi Province, People’s Republic of ChinaCorrespondence: Guodu Tang, Department of Gastroenterology, The First Affiliated Hospital of Guangxi Medical University, 22 Shuangyong Road, Nanning City, Guangxi Province, People’s Republic of China, Tel +86 13739139408, Email tangguodu@stu.gxmu.edu.cnBackground: The pathogenesis of acute pancreatitis (AP) and the relationship between acute pancreatitis and hypertriglyceridemia are complex and not fully understood. The purpose of this study was to identify the hub genes along with common differentially expressed genes (DEGs) between acute pancreatitis and hypertriglyceridemia.Methods: We downloaded three gene expression profiles of AP and one gene expression profile of hypertriglyceridemia from the Gene Expression Omnibus (GEO) database and filtered the DEGs based on the above four datasets. Next, we identified the hub genes by performing the Gene Ontology (GO) term analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, and protein–protein interaction (PPI) construction. We also constructed the miRNA-hub gene network and established mouse models with hypertriglyceridemia and AP using a high-fat diet and injection of caerulein (CAE), respectively. Finally, the immunohistochemical analysis was used to verify the differential expressions of hub genes in AP, hypertriglyceridemia, and normal pancreatic tissue.Results: A total of 105 DEGs associated with AP and 149 DEGs associated with hypertriglyceridemia were identified. Additionally, we identified six hub genes of AP, all of which were closely related to the cytoskeleton while two DEGs genes were common in both AP and hypertriglyceridemia. We also verified their expression in mouse models. Finally, a network of miRNA-mRNA was also constructed, and the top seven interactive miRNAs (hsa-mir-1– 3p, hsa-mir-5195– 3p, hsa-mir-145– 5p, hsa-let-7b-5p, hsa-mir-10b-5p, hsa-mir-206, and hsa-mir-613) targeting the most hub genes were identified.Conclusion: Overall, we identified six hub genes associated with AP and two common DEGs associated with AP and hypertriglyceridemia along with seven miRNAs that may regulate AP. This study could provide new ideas for further elucidation of the pathogenesis of hypertriglyceridemia-induced acute pancreatitis in the future.Keywords: acute pancreatitis, biomarkers, hypertriglyceridemia-induced pancreatitis, bioinformatics